STRATEGI KOMUNIKASI PEMASARAN TERPADU KELOMPOK SADAR WISATA DI DESA NGLANGGERAN, YOGYAKARTA - Fahreza Anugrah Putra (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Village development is a tourism development program that is one of the Government’s efforts to follow up on strategic issues in national economic growth because tourism is the main pillar and the largest foreign exchange earner. Nglanggeran Tourism Village is one of the leading tourist villages in Yogyakarta, Indonesia, and is able to provide economic activities to be temporarily suspended, the Tourism Awareness Group (Pokdarwis) is required to be able to carry out planning and an integrated marketing communication strategy. This study uses a case study method with qualitative descriptive approach. Data collection through in-depth interviews, observation, and literature study. The results of this study show that the most effective communication channels used by Pokdarwis are Direct Marketing, Wod of Mouth, Events and Experiences, compared to Sales Promotion, Public Relations, Personal Selling, Advertising, and Interactive Marketing.